Intangible economy : how services shape global production and consumption - Deborah K Elms; Hassani, Arian Low, Patrick (New Delhi Cambridge University Press, 2017)
The Intangible Economy: How Services Shape Global Production and Consumption studies aspects of the role of services in development as well as on particular sectoral issues, always with policy considerations lurking not far from the analysis. The volume highlights the evolution and significance of services in the global economy, including as a vehicle for development. It discusses the major pillars that hold the services infrastructure together, namely, its governance and financing mechanisms. Other chapters adopt more specific geographical or sectoral perspectives, including a regional study of the impact of services in economic integration in ASEAN; a country-level analysis of the role of services in economic and social upgrading in India; a look at industry-specific dynamics through the business process outsourcing model; and finally, a value chain view to understand how services are impacted on a granular or micro level by policies.
Keywords: Production